1990
DOI: 10.1164/ajrccm/142.4.843
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos Content of Lung Tissue, Lymph Nodes, and Pleural Plaques from Former Shipyard Workers

Abstract: Autopsy samples from eight former shipyard workers were collected from lung parenchyma, tracheal lymph nodes, and pleural plaques. The tissue from each respective area was prepared by a modified bleach digestion technique, and the residue was collected on a 0.2-micron pore polycarbonate or 0.22-micron mixed cellulose ester filter. Quantitation of ferruginous bodies and uncoated fibers was done by light and transmission electron microscopy, respectively. Differences in the asbestos burden were noted for each si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(88 citation statements)
references
References 8 publications
4
81
0
3
Order By: Relevance
“…However, many studies have shown the existence of asbestos bodies, fibers of asbestos coated with an iron-rich material, in regional lymph nodes [31,32]. It has also been reported that nonoccupationally and occupationally asbestos-exposed individuals have asbestos in their lymph nodes [33][34][35]. Therefore, it is probable that NK cells suffer the harmful effects of asbestos in lymph nodes as well as in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have shown the existence of asbestos bodies, fibers of asbestos coated with an iron-rich material, in regional lymph nodes [31,32]. It has also been reported that nonoccupationally and occupationally asbestos-exposed individuals have asbestos in their lymph nodes [33][34][35]. Therefore, it is probable that NK cells suffer the harmful effects of asbestos in lymph nodes as well as in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of persistence in animal models is discussed at length elsewhere in these proceedings. Table 1 lists published studies that supply information on the relative proportion of chrysotile and amphiboles found in lung samples (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The preparative methods, types of electron microscope, and counting rules used in studies differ markedly, and these differences undoubtedly affect the results.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of fibrils would increase due to fiber splitting [47,49,50], possibly together with the carcinogenic effect, as the split fibrils can move to the pleura [45,47,48]. Asbestos fibers have been identified in the pleura by autopsy, chrysotile being the predominant asbestos form found in pleural plaques [51] and pleural/mesothelial tissues in general [46,52]. In a singular contradicting report amphibole fibers outnumbered chrysotile ones in anthracotic "black spots" in the parietal pleura sampled during thoracoscopy from all 14 studied individuals [53].…”
Section: Page -02mentioning
confidence: 99%